Remediation and stabilization of contaminated subsoil under existing buildings – case study - Ewa Iwanicka; Sylwia Janiszewska; Eugeniusz Koda (Acta Scientiarum Polonorum. Architectura)
In order to reduce the amount of impurities in the ground under the existing buildings, the combined use of purification system of ground and ground water remediation process allow optimization depending on the type of soil and water and the type of contamination. In-situ soil treatment methods are characterized by low costs and are particularly useful for cleaning large surfaces. However, applying them under the existing buildings entails increased costs of soil purification. In-situ soil treatment methods can be applied in urbanized or industrial areas, under building constructions, in the nearby development or under roads, etc., even when there are infrastructure installations in the contaminated ground layers. The effectiveness of remediation depends on the proper selection of the method to be used taking into account the amount and type of contaminants present in the studied area, the geological structure of the area, the location of aquifers and the direction of ground water flow. The aim of this article is to present the in-situ soil remediation methods, which, due to the high effectiveness of removing the most common types of contamination, are applied to the existing infrastructure. The article presents two methods of soil purification on site, the choice of which has been conditioned by the type of soil contamination. The increased content of the surface layer in the area of petroleum substances was neutralized by bioremediation, while in the case of detection of increased content of heavy metals in the form of arsenic at the construction site, the stabilization method designed was used. Due to properly conducted reconnaissance of the area before commencing works, as well as monitoring of the purification process, it was possible to observe the neutralization of pollution occurring in a controlled manner.